Behavior of fast earthward flow near the braking region: Hall MHD simulation. (29th November 2016) - Lu, Xingqiang; Ma, Zhiwei; Guo, Wei
Abstract: Behavior of the fast earthward flow near the braking region in the magnetotail during a substorm is investigated using the Hall MHD simulation. The results indicate that the high-speed earthward plasma flow is associated with fast reconnection in the middle tail. The fast flow is mainly confined in the range . In the region of, due to intermittent magnetic reconnection, the earthward flow exhibits a fluctuating property, i.e., the flow is localized in space and is bursty in time. The pile-up of the magnetic flux and plasma in the near-Earth region leads to formation of the fast-flow braking region or dipolarization front. After colliding into the fast-flow braking region, a part of the Earth flow bounces back, and leads to an intermittent tailward flow in the near-Earth magnetotail.